Analisis Tafsir Bahr Al-‘Ulum Karya Abu Al-Laits Al-Samarqandi - Rahmaifa Nasyah; Nada Ramadhania; Dea Ananda Wilianca; Lukmanul Hakim (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2025)
This study thoroughly examines seven important components in Tafsir Bahr al-‘Ulum by Abu al-Laits al-Samarqandi, namely the mufassir’s biography, interpretation methods, style, structure, characteristics, sources of reference, and concrete examples of interpretation. This book is one of the classical tafsirs rich in scientific and linguistic approaches. The main objective of this research is to analyze the systematic structure, approach, and characteristics of this tafsir in explaining the verses of the Qur’an. This study employs a qualitative method with a literature review approach, analyzing the primary source, Bahr al-‘Ulum, along with secondary references that discuss the author’s thoughts and interpretations. The findings show that this tafsir uses a tahlili method, meaning it explains the Qur’anic verses systematically and sequentially. Additionally, the tafsir has a scientific style with linguistic, qira’at (Qur’anic recitation), and some philosophical and medical aspects. However, one weakness identified is Abu al-Laits al-Samarqandi’s tendency to cite Isra’iliyyat narrations without strict selection. Nevertheless, Bahr al-‘Ulum remains an important tafsir in the Islamic scholarly tradition because of its deep analysis of verse meanings and its relevance to understanding Islamic law and spiritual values. Keywords : Analysis, Tafsir Bahr al-‘Ulum, Al-Samarqandi